2012
DOI: 10.1080/14786435.2011.630691
|View full text |Cite
|
Sign up to set email alerts
|

Shearing of γ′ precipitates in Ni-base superalloys: a phase field study incorporating the effective γ-surface

Abstract: An extended Phase Field Model of Dislocations in Ni-base superalloys is presented. It incorporates the recently developed effective γ-surfaces for both matrix and precipitate phases, obtained from atomistic simulations. These novel γ-surfaces feature extrinsic stacking faults as additional local minima. Thus, they offer an increased number of available dislocation dissociation pathways within the phase field system. The new model has been used to simulate a variety of mechanisms for γ precipitate shearing prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Quite remarkably, this extended intrinsic fault terminates as a narrow extrinsic stacking fault. The local displacements associated with this fault are consistent with the CESF-1 structure predicted by the EAM [11] and PFMD models [9,10]. The Burgers circuit traced around the entire CESF-1 segment requires a closure displacement that is consistent with an edge dislocation on the primary slip system, with b= a 3 [112].…”
Section: Superlattice Faults and Terminating Partialssupporting
confidence: 51%
See 1 more Smart Citation
“…Quite remarkably, this extended intrinsic fault terminates as a narrow extrinsic stacking fault. The local displacements associated with this fault are consistent with the CESF-1 structure predicted by the EAM [11] and PFMD models [9,10]. The Burgers circuit traced around the entire CESF-1 segment requires a closure displacement that is consistent with an edge dislocation on the primary slip system, with b= a 3 [112].…”
Section: Superlattice Faults and Terminating Partialssupporting
confidence: 51%
“…The structure of the latter can be thought of as SISF over CISF. Both atomistic simulations [7] and the Phase Field Model of Dislocations (PFMD) [8][9][10] have shown that the a 3 112 dislocations are indeed likely to be dissociated. Both complex faults have a very high fault energy [11], and as a result the bounding Shockley partial pair would have such a small separation that when observed using conventional TEM imaging, they would appear as a single a 3 112 dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work imaging the terminating dislocations of SISFs in single-crystal alloys (Vorontsov et al, 2012a(Vorontsov et al, , 2012b has shown conclusively that the former structuredFigure 8(c)dis correct. Similarly an SESF, itself already consisting of faults on two adjacent layers, is terminated by a CISF and two closely spaced partials, as illustrated in Figure 8(d).…”
Section: Dislocations In the L1 2 Phasementioning
confidence: 92%
“…Kovaric et al (2009) have made phase field simulations of such dislocation dissociation at the g/g 0 interfaces to leave a stacking fault in the matrix and no planar defect in the precipitate; however, the volume fraction of g 0 was rather low and therefore the calculations are probably more relevant to polycrystalline superalloys. Recently, Vorontsov et al (2012aVorontsov et al ( , 2012b have relaxed this limitation to demonstrate the effects of fault energy and precipitate shape, for a g 0 fraction typical of a single-crystal superalloy. …”
Section: Role Of Stacking Fault Shear In Primary Creep Deformationmentioning
confidence: 98%
“…It is noticeable that the fastest fault (CESF-SESF) is also the one with the highest stacking fault energy C, which may be unexpected (C CESFÀ2 >C CISF >C APB > C SISF >C SESF ). [33] This may be caused by the additional combined effect of the reordering process present in the CESF/SESF lengthening. [13,28] The reordering process can reduce the amount of segregation needed and therefore provide higher lengthening rates for CESF/SESF than the other two mechanisms.…”
Section: Calculated Velocitiesmentioning
confidence: 99%